2016
DOI: 10.1371/journal.pntd.0004486
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Dog Rabies Vaccine and Registration in Ilocos Norte, Philippines (2012)

Abstract: BackgroundThe Philippines is one of the developing countries highly affected by rabies. Dog vaccination campaigns implemented through collaborative effort between the government and NGOs have played an important role in successfully reducing the burden of disease within the country. Nevertheless, rabies vaccination of the domestic animal population requires continuous commitment not only from governments and NGOs, but also from local communities that are directly affected by such efforts. To create such long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
19
2
Order By: Relevance
“…This constraint can be overcome if the cost of vaccination is determined by dog-owners’ willingness to pay. In the Philippines, dog-owners were only willing to pay USD 1.67 for dog rabies vaccination [ 18 ]. To better assess the variations in the socio-economic determinants of vaccination in the populations living in the rabies endemic areas, such surveys needs to be conducted in other locations in the DRC.…”
Section: Resultsmentioning
confidence: 99%
“…This constraint can be overcome if the cost of vaccination is determined by dog-owners’ willingness to pay. In the Philippines, dog-owners were only willing to pay USD 1.67 for dog rabies vaccination [ 18 ]. To better assess the variations in the socio-economic determinants of vaccination in the populations living in the rabies endemic areas, such surveys needs to be conducted in other locations in the DRC.…”
Section: Resultsmentioning
confidence: 99%
“…Cost was the main limiting factor for human PEP access among study participants; it should be expected that if access to canine vaccine is addressed, cost would surely be a limiting factor that would need to be considered. Future assessments should attempt to identify explanatory variables for this finding [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 A study in the Philippines showed that the WTP for a dog rabies vaccine was influenced by vaccine price, SES, and knowledge about rabies. 26 Another study also found that vaccine price, knowledge, and SES were the predictors for WTP for vaccination, in this case against tick-borne encephalitis in Sweden. 27 In the context of human papillomavirus vaccine, a study in Nigeria found that vaccine price and experienced illness influenced WTP.…”
Section: Factors Associated With Willingness To Pay For Dengue Vaccinementioning
confidence: 92%